Return-to-competition criteria after ulnar collateral ligament reconstruction: A systematic review and meta-analysis - Anderson, M. J. J.; Crockatt, W. K.; Mueller, J. D.; Hellwinkel, J. E.; Alexander, F. J.; Trofa, D. P.; Ahmad, C. S. (The American Journal of Sports Medicine, 2022)
Background: Injury to the ulnar collateral ligament of the elbow is common among overhead throwing athletes and can result in significant functional limitations. While surgical reconstruction offers high rates of return to competition, there are no validated or universally accepted guidelines for determining when an athlete can safely resume play.